Pengaruh Brand Association terhadap Brand Loyalty yang dimediasi oleh Brand Trust Pengguna GoPay di Kabupaten Bandung Barat - Muhammad Saijunus; Siti Herawati (Studi Ilmu Manajemen dan Organisasi, 2022)
Purpose: To determine the effect of brand association on brand loyalty mediated by  brand trust of GoPay users in West Bandung Regency is the aim of this reseach. Research methodology: This study used a quantitative approach with the object of GoPay. Data collected using an electronic questionnaire that has been tested for validity and distributed to 120 respondents. Data analysis used simple regression formula, multiple regression, and Sobel test. Results: The results showed that the brand association positive and significant impact on brand trust and brand loyalty, and brand trust is also positive and significant effect on brand loyalty, and brand trust mediating the effect of brand associations on brand loyalty. Limitations: This study is limited by population characteristics and loci, namely people who live in West Bandung Regency with an age range of 17 to 35 years. Contribution: Based on the results of the study, it can be concluded that GoPay needs to pay attention and improve their brand association properly to increase brand trust and brand loyalty to GoPay users.